Pain and suffering in medieval theology: academic debates at the University of Paris in the thirteenth century - Mowbray, Donald (Boydell Press, 2009)
Thirteenth-century theological ideas about human pain and suffering and the Passion of Christ -- Gendering pain : theological ideas about female and male suffering -- Pain as a restorative power : voluntary suffering and satisfaction for sin -- The intellectual development of limbo : pain, children and original sin -- Anima separata : masters of theology and the controversy surrounding the suffering of the separated soul -- Defining the corporeal : suffering in hell according to masters of theology at Paris, c. 1230-c. 1280